A Spatially Detailed Projection of Environmental Conditions in the Arctic Initiated by Climate Change - Alexander Kislov; Ali Alyautdinov; Alisa Baranskaya; Nataliya Belova; Daria Bogatova; Marina Vikulina; Irina Zheleznova; Galina Surkova (Atmosphere, 2023)
The environmental conditions of the Arctic are vulnerable to the effects of climate change. We focus on the territory of the Yamalo-Nenets Autonomous Okrug (YaNAO). The objective of this study is to project mid-21st century climate-driven changes in the state of climate and the natural environment in the YaNAO. For this purpose, the CMIP6 data models with the climate change scenario SSP5-8.5 were used. Climate change directly affects the statistics of extreme events and climatically driven phenomena, such as frosts and thaws, as well as avalanches and slush flows. Climate change causes changes in the Arctic environment, primarily due to permafrost degradation, leading to important modifications in events such as mudflows, cryogenic landslides, abrasion, erosion, suffusion, frost heave, solifluction, thermokarst, and others. In some cases, the intensity and area of these processes increase, such as heaving processes and thermokarst becoming more active by 2050. In other cases, the solifluction processes decrease in the south part of the YaNAO due to the discontinuous or sporadic permafrost distribution. Projected climatic changes will inevitably lead to the restructuring of the geosystems in YaNAO, creating risks for infrastructure in economically active territories.